Volleyball Receiving Ability at PORPROV 2022: Effectiveness Analysis - Kelvin Jaramias Grasiano; Eka Supriatna; Rubiyatno Rubiyatno (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. This study aimed to assess the receiving ability in the 2022 provincial volleyball championship and determine the extent to which the use of receiving techniques contributes to producing points and plays a role in the game. Materials and methods. This study employed a quantitative approach utilizing survey methods in addition to direct observation of matches in the field. A sample of athletes who utilized basic receiving techniques in the top eight competitions, semifinals, competition for third and fourth place, and finals were selected using purposive sampling techniques. The data was collected using a rubric assessing basic receive techniques, and the analysis was conducted using descriptive percentages with the assistance of Microsoft Excel 2016 software. Results. According to the data analysis, the District's receiver performance was found to be very ineffective in the top 8 matches, with an average effectiveness of 27%. The semifinal match also showed a very ineffective performance with an average effectiveness of 23%. Similarly, the final match for 3rd and 4th place had an average effectiveness of 19% in the very ineffective category. The final match for the 1st and 2nd place winners had an average effectiveness of 21% in the very ineffective category. Therefore, based on the research data, it can be concluded that the effectiveness of the 2022 Proprov Championship volleyball receiving ability is extremely poor, as per the reference category. Conclusion. The results of this data provide valuable insights for coaches looking to enhance the training of volleyball athletes' basic receiving techniques. By using this information as a benchmark, coaches can tailor their coaching methods to improve the athletes' skills and knowledge, while also introducing variations to the training program to ensure continued progress and development.